2012
DOI: 10.1002/14651858.cd006469.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy for metastatic and recurrent cervical cancer

Abstract: Combination cisplatin-based chemotherapy could be a viable option for patients of good performance status with recurrent/metastatic cervical cancer, but further trials that report adequate survival and QoL data are sought. Response rates and improvements in survival are low. Cisplatin-based combinations have significant toxicity. Outcomes are poor and novel cytotoxic/biological agents and optimal scheduling need further investigation. Future trials need to stratify for and perform planned subgroup analysis wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
1
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 43 publications
2
48
1
6
Order By: Relevance
“…Reports of an excellent complete response in metastatic cervical cancer are rare. A review on chemotherapy for metastatic and/or recurrent cervical cancer (Scatchard et al, 2012) found that in two randomized control studies, the median survival of patients after single agent cis-platin chemotherapy for metastatic disease was 17 (Alberts et al, 1987) and 13 (Cadron et al, 2005) months respectively. It is therefore interesting to speculate as to whether the DC vaccine had a contributory role in this patient achieving a sustained disease free status.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of an excellent complete response in metastatic cervical cancer are rare. A review on chemotherapy for metastatic and/or recurrent cervical cancer (Scatchard et al, 2012) found that in two randomized control studies, the median survival of patients after single agent cis-platin chemotherapy for metastatic disease was 17 (Alberts et al, 1987) and 13 (Cadron et al, 2005) months respectively. It is therefore interesting to speculate as to whether the DC vaccine had a contributory role in this patient achieving a sustained disease free status.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical cancer remains a significant public health concern worldwide (2,5,6), particularly among women aged ≤65 years or in developing countries (11)(12)(13). Approximately one-third of patients with invasive, recurrent, or metastatic cervical cancer eventually succumb to the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In a Cochrane database review, Scatchard et al [10] analyzed 10 randomized trials assessing 1,438 participants. There was no statistically significant difference in response rate between women who received single-agent chemotherapy and those who received combination therapy (response rate 0.94, 95% CI 0.57-1.55).…”
Section: Kumar/guptamentioning
confidence: 99%